2012
DOI: 10.1007/s10620-012-2269-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Pancreatic Duct Stent or Guidewire Facilitates Bile Duct Access with Low Rates of Precut Sphincterotomy: A Randomized Clinical Trial

Abstract: Use of a PDS or PDW facilitates CBD cannulation while maintaining a low complication rate and reducing the need for precut sphincterotomy in the majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…In addition, a retrospective study suggests that PS‐WGC can be a salvage technique for cases with difficult biliary cannulation . Considering the increased difficulty in biliary cannulation in cases with a small ampulla during PS‐WGC (the rate of difficult cannulation was 86% within the group), DGW technique, or additional precut sphincterotomy over a pancreatic stent may be an option for these cases …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a retrospective study suggests that PS‐WGC can be a salvage technique for cases with difficult biliary cannulation . Considering the increased difficulty in biliary cannulation in cases with a small ampulla during PS‐WGC (the rate of difficult cannulation was 86% within the group), DGW technique, or additional precut sphincterotomy over a pancreatic stent may be an option for these cases …”
Section: Discussionmentioning
confidence: 99%
“…In PS‐WGC, we can readily place a pancreatic stent and avoid the injury to the pancreatic parenchyma during ERCP. Although the potential effectiveness of PS‐WGC has been reported in terms of biliary cannulation success, there is a paucity of evidence on prevention of PEP …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more precut sphincterotomies were performed with the pancreatic stent-assisted technique (26% vs 10%), likely accounting for the higher cannulation success. 20 A retrospective study of 76 patients showed similar efficacy (93% success, 21% requiring precut). 21 The placement of a pancreatic stent immediately, although helpful for precut, can often compress the biliary orifice and make standard approaches more difficult.…”
Section: Pancreatic Duct Techniquesmentioning
confidence: 90%
“…78,79 The risk of PEP (5%) was acceptable with this method while the need for precut sphincterotomy may be increased (> 25%). 80 Needle knife fistulotomy (NKF), whereby the cut is initiated away from the papillary/pancreatic orifice, is perhaps a safer precut method with regard to PEP. 47 A PRCT comparing NKF to NKS reported no cases of PEP after NKF compared to only 7.6% for NKS but one fatality occurred.…”
Section: Procedures Techniquesmentioning
confidence: 99%